(untitled) (Heritage, 2021)
Education has always been socially conditioned. On the one hand, everything that happens in society necessarily reflects on the education process, and on the other hand, all changes in education cause changes in society. Bastina journal, which used to be published by the Institute for the Study of Culture of Serbs, Montenegrins, Croats and Muslims in Pristina from 1991 to 1997, and by the Institute for Serbian Culture in Pristina since 1998, which has now been based in Leposavic since 1999, publishes papers in the field of social and humanistic sciences. These papers most often discuss topics in the field of Literature, History, History of Culture, Ethnology, Political Science and Sociology, and occasionally in the field of Ethnomusicology, Demography, Archeology, Art, Art History, Language, Literature and Aesthetics, while one journal issue published a special topic – Vladeta Vukovic’ Works. The journal has so far also included Discussions and Review, Chronicles and Composition. In this paper, the co-authors investigate the representation of education-related topics, as well as the character, scope and intensity of these topics in the Bastina Journal from the first edition in 1991 to the latest edition in 2020. A retrospective study of scientific and professional papers showed that a total of 63 papers were published that directly and indirectly study education, primarily in the field of the history of pedagogy, general pedagogical topics and other education-related issues. These topics were mostly published within the History of Culture pillar. As a separate topic, Education was present only in two issues in 2007 and in one issue in 2009 and in the last two issues in 2020 within the Pedagogy course.